Impella 5.0 ® as bridge-to-recovery short-term mechanical circulatory support after LVAD explantation - Oßwald, Anja; Schmack, Bastian; Goldwasser, Ranny; Kreußer, Michael; Raake, Philip; Karck, Matthias; Ruhparwar, Arjang (Journal of thoracic disease, 2019)
A 56-year-old male presented in critical state of heart failure treated by an extracorporeal life support system (ECLS). He was transferred to our hospital for evaluation of left ventricular assist device (LVAD) implantation. Echocardiographic findings showed a severely impaired left ventricular function with an ejection fraction (EF) of 15% and normal right ventricular function.
Gesehen am 23.07.2019
® im Titel ist hochgestellt